The American Public Health Association Endorses Single-Payer Health System Reform. Issue 6 (26th June 2022) - King, Ben; Spadaro, Anthony; Schiff, Gordon; Rodriguez-Monguio, Rosa; Jordan, Alison O.; Flaherty, Lisa; Lee, Wei-Chen; Zito, Julie; Fein, Oliver; ,
Abstract : Health care is a human right. Achieving universal health insurance coverage for all US residents requires significant system-wide reform. The most equitable and cost-effective health care system is a public, single-payer (SP) system. The rapid growth in national health expenditures can be addressed through a system that yields net savings over projected trends by eliminating profit and waste. With universal health insurance coverage through SP financing, providers can focus on optimizing delivery of services, rather than working within a system covered by payers who have incentives to limit costs regardless of benefit. Rather, with a SP, the people act as their own insurer through a partnership with provider organizations where tax dollars work for everyone. Consumer choice is then based on the best care to meet need with no out-of-pocket payments. SP financing is the best option to ensure equity, fairness, and public health priorities align with medical needs, providing incentives for wellness. Consumer choice will drive market forces, not provider network profits or insurer restrictions. This approach benefits public health, as everyone will have universal access to needed care, with treatment plans developed by providers based on what works best for the patient. In 2021, the American Public Health Association adopted a policy statement calling for comprehensive reforms to implement a SP system. The proposed action steps in this policy will help build a healthier nation, saving lives and reducing wasted health care expenditures while addressing inequities rooted in social, demographic, mental health, economic, and political determinants.